A comparison between incremental cadence and resistance cycling VO2 max testing protocols for trained cyclists - Deakin, G. B.; Zhou, S.; Davie, A. J. (2001)
Maximal oxygen uptake (VO2 max) studies using cycle ergometers have traditionally used incremental resistance protocols (RP) at a constant cadence. The purpose of this study was to evaluate whether an incremental cadence protocol (CP), using a constant resistance relative to gross-body-mass was equally effective and reliable in eliciting VO2 max as an incremental resistance protocol in trained cyclists. Ten trained male cyclists/triathletes, aged 25.2±6.8 years, completed two CP and one RP trials in a random order over a three-week period. The CP started at a relative workload of 2.75 W per kg of gross-body-mass, with the cadence increased by 10 rpm each minute from the initial cadence of 70 rpm. The RP started from an initial 125 W with the workload increased by 25 W each minute whilst keeping a constant cadence of 90 rpm. All tests were conducted on a mechanically braked cycle ergometer (Monark 868) in an air-conditioned laboratory. No significant differences were found between the CP (mean value of the two CP trials) and RP for the variables of VO2max (3.9±0.6 vs 4.0±0.8 L.min-1), peak ventilation (140.5±22.8 vs 143.0±27.1 L.min-1), or post-exercise blood lactate (11.4±2.1 vs 11.9±1.6 mmol.L-1), respectively. The peak heart rate (183.9±10.5 vs 187.5±11.4 b.min-1) and peak workload (319.9±60.2 vs 375.1±67.3 W) were significantly less (p<0.05) less for the CP than the RP, respectively. For the two CP trials the test-retest reliability Intra-class Correlation Coefficient was 0.96, the Technical Error of Measurement (TEM) was 0.17 L.min-1 and the relative TEM was 4.35%. The results indicate that the incremental CP is equally effective in eliciting VO2 max as the incremental RP and is a reliable method of measuring VO2 max in trained cyclists.